Answer:
a = - 13, b = - 10
Explanation:
Given that x = - 1 and x = - 2 are zeros then
f(- 1) = 0 and f(- 2) = 0, that is substituting value into the polynomial
f(- 1) = (- 1)³ - 2(- 1)² - a + b = 0 , that is
- 1 - 2 - a + b = 0
- a + b = 3 → (1)
f(- 2) = (- 2)³ - 2(- 2)² - 2a + b = 0, that is
- 8 - 8 - 2a + b = 0
- 2a + b = 16 → (2)
Multiply (1) by - 2
2a - 2b = - 6 → (3)
Add (2) and (3) term by term to eliminate a
- b = 10 ( multiply both sides by - 1 )
b = - 10
Substitute b = - 10 into (1) and evaluate for a
- a - 10 = 3 ( add 10 to both sides )
- a = 13 ( multiply both sides by - 1 )
a = - 13